2015
DOI: 10.1002/ange.201502699
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Exchange in Porous and Dense Magnesium Borohydride

Abstract: Magnesium borohydride (Mg(BH 4 ) 2 )i so ne of the most promising complex hydrides presently studied for energyrelated applications.M any of its properties depend on the stability of the BH 4 À anion. The BH 4 À stability was investigated with respect to H!Dexchange.Insitu Raman measurements on high-surface-area porous Mg(BH 4 ) 2 in 0.3 MPaD 2 have shown that the isotopic exchange at appreciable rates occurs already at 373 K. This is the lowest exchange temperature observed in stable borohydrides.G as-solid i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The isotopic exchange seems to start at 81 C as a new peak appears at 1718 cm À1 and corresponding to the reported region of symmetric B-D stretching (n B-D ). 43 This characteristic peak for B-D stretching is observed at a lower temperature than that reported by Zavorotynska et al 31 As previously reported, 31 this observation is supported by a decrease in 2v 4 and red shi in v 1 . The latter observation can be explained by the fact that the peak at $2318 cm À1 actually consists of several overlapping peaks, and is dominated by n 1 in pure Mg(BH 4 ) 2 .…”
Section: In Situ Raman Spectroscopy and Adsorption Studiessupporting
confidence: 70%
See 2 more Smart Citations
“…The isotopic exchange seems to start at 81 C as a new peak appears at 1718 cm À1 and corresponding to the reported region of symmetric B-D stretching (n B-D ). 43 This characteristic peak for B-D stretching is observed at a lower temperature than that reported by Zavorotynska et al 31 As previously reported, 31 this observation is supported by a decrease in 2v 4 and red shi in v 1 . The latter observation can be explained by the fact that the peak at $2318 cm À1 actually consists of several overlapping peaks, and is dominated by n 1 in pure Mg(BH 4 ) 2 .…”
Section: In Situ Raman Spectroscopy and Adsorption Studiessupporting
confidence: 70%
“…The observed B-D modes are in good agreement with literature. 31,32 S1-D and S2-D have gained the most in intensity in B-D stretching followed by S4-D and S3-D, when comparing the B-H stretching mode n 3 and combined B-D stretching modes n B-D aer H / D exchange. These observations give a rst indication on the extent of exchange aer 23 h and imply that the pure materials may have higher exchange rates than those with additives.…”
Section: Spectroscopic Studiesmentioning
confidence: 95%
See 1 more Smart Citation